Perencanaan dan Simulasi Poros Roda Traktor Tangan - Misar, Misar; Sudarsono, Sudarsono; Samhuddin, Samhuddin (Teknik Mesin Universitas Halu Oleo, 2018)
This study aims to determine safe and good shaft planning, stress distribution. In this study it was designed using Autodesk Inventor software and simulation using software Ansys Workbench 18.1. The material used to plan the shaft is carbon steel for machine construction and cold steel rod steel for the shaft with the S55C symbol with a tensile strength of 647,46 N/mm2. Results shaft planning calculations showed that the plan 9.372 kwpower, torque or torque with a lap 136.73 rpm of 654.25 Nm, the permitted voltage obtained a value of 83 N/mm2. The shear stress that occurs on the shaft is 44.9 N/mm2, from the calculation results itcan be seen that the shear stress that occurs is smaller than the required voltage (????<????????), where is ???? = 44.9 N/mm2 and ????????=83N/mm2, so it can be concluded that the planned ossizeis quite safe. Bending stress shaft that occurs in manual calculation 56.25 N/mm2 and the simulation 61.291 N/mm2, this value is still below the value of the permit voltage of 83 N/mm2, then the shaft planning is quite safe. The maximum shaft shear stress that occurs in manual calculations is 52.98 N/mm2 and in the simulation of 34,624 N/mm2, this value is still below the value of the permit voltage of 83 N/mm2, the shaft planning is quite safe. Keywords: Planning shaft, safe and good shaft, simulation, ansys workbench,distribution voltage.